2006
DOI: 10.3758/bf03193412
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the seductive details effect in terms of working memory capacity

Abstract: Previous work on learning from text has demonstrated that although illustrated text can enhance comprehension, illustrations can also sometimes lead to poor learning outcomes when they are not relevant to understanding the text. This phenomenon is known as the seductive details effect. The first experiment was designed to test whether the ability to control one's attention, as measured by working memory span tasks, would influence the processing of a scientific text that contained seductive (irrelevant) images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
172
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(197 citation statements)
references
References 46 publications
11
172
3
Order By: Relevance
“…This possibility can be further investigated by combining an eye-tracking technique with selfreports regarding interest in particular animals. Importantly, pictures with aggressive-looking animals do not appear to distract pupils from learning (Sanchez & Wiley, 2006) as higher information retention scores were obtained compared with neutral-looking animals.…”
Section: Information Retention Concerning Aggressive-looking Animalsmentioning
confidence: 94%
See 1 more Smart Citation
“…This possibility can be further investigated by combining an eye-tracking technique with selfreports regarding interest in particular animals. Importantly, pictures with aggressive-looking animals do not appear to distract pupils from learning (Sanchez & Wiley, 2006) as higher information retention scores were obtained compared with neutral-looking animals.…”
Section: Information Retention Concerning Aggressive-looking Animalsmentioning
confidence: 94%
“…Presentation of animals in science textbooks may contain these aggressive cues, but it is not clear whether these cues influence learning. On the one hand, fear may enhance learning (e.g., Chapman et al (2013), but on the other hand, if aggressive pictures attract more attention, it can be argued that they also distract the pupil from learning (Sanchez & Wiley, 2006). Furthermore, visual exposure to colour photographs of animals positively influenced the willingness to protect them (Štefaniková & Prokop, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…age [3], gender [4], qualifications/grades [5] -but do little about once activities and materials have been prepared, and others -e.g. reading ability [6], working memory capacity [7], extroversion and introversion [8] -which we can ascertain through testing but probably do even less to accommodate at a distance. Hence, making design adjustments for known disciplinary differences can represent a pedagogic quick-win for both institutions and their students.…”
Section: Introductionmentioning
confidence: 99%
“…However, other relevant studies indicated that students face great difficulty when they interact with visual material (Bodemer et al 2005; Hannus and Hyönä 1999; Hegarty and Just 1993) Specifically, research has shown that learners often emphasize the verbal text"s content and ignore the images or superficially skimm through them (Cromley et al 2010). Moreover, evidence from eye-tracking studies indicates that learners better comprehend images when they devote more time to relevant elements of the images, than to irrelevant ones (Sanchez and Wiley 2006).…”
Section: Introduction the Role Of Images In Science Multimedia Textsmentioning
confidence: 99%